Numerical approach to controlling a moving jet’s vibration in an electrospinning system: An auxiliary electrode and uniform electric field - Chen, Rouxi; Wu, Yuke; Fan, Jie; Wang, Liang; Su, Zhibo; Qin, Liming; Liang, Libing; Li, Yantao; Cheng, Jianhua; Liu, Yong (Journal of low frequency noise, vibration, and active control, 2019)
A variational principle is established for a moving jet in the electrospinning process to study the vibration property of the jet. A higher accelerated velocity and lower vibration frequency are needed in a multi-needle electrospinning system. This paper introduces an auxiliary electrode to enhance the electric strength, and a numerical analysis is carried out to design an optimal electric field.